Establishing the genetic variation in physiological response in response to heat stress in semi-arid region in Jamunapari goats. Issue 1 (2nd January 2020) - Kaushik, Rakesh; Goel, Anjana; Rout, Pramod Kumar
ABSTRACT: The genetic variation in physiological response was analysed at population level in Jamunapari goats. The temperature humidity index (THI) range varied from 82.00 to 92.08 during hot period, 49.96 to 59.68 during cold period and 65.32 to 74.00 during thermo-neutral period. Physiological responses were recorded for 695, 617 and 291 animals during the hot, cold and thermo-neutral period, respectively. The sire mean of heat stress-susceptible (HSS) and heat stress-tolerant (HST) families differed by 19.737 in respiration rate (RR) and 31.438 in heart rate (HR). RR and HR were significantly different (P < 0.01) between HSS and HST phenotype. However, rectal temperature (RT) did not differ significantly (P < 0.01) between HSS and HST phenotype. The heritability of RT, RR and HR were 0.180 ± 0.058, 0.077 ± 0.044 and 0.307 ± 0.076, respectively. Genetic correlation between RT and HR  was high during hot and cold period. The genetic correlation between RT and HR was high and positive during hot and cold period. The phenotypic correlation between RT and HR ranged from 0.132 to 0.190. The genetic correlation between RT with other traits  was low and negative. Our finding indicates that phenotypic difference can be heritable.